An attempt at a typology of karst lakes in the Połaniec Basin (Małopolska Upland) - Stachura, Michał; Wieczorek, Dariusz; Zieliński, Artur (Bulletin of Geography. Physical Geography Series, 2018)
The main goal of the paper is to attempt a typology of karst lakes in the Połaniec Basin (Małopolska Upland). The typology was conducted on the basis of a dependence analysis of several essential morphometric parameters of lake basins. The considered data comprised 23 lakes with respect to15 morphometric features. The correlation analysis, mainly in a group of lakes that are located in single karst sinkholes, revealed that length and width of basins are distinctly associated features. It is also noticeable that basin shape determines lake volume, even though pools, that are characterised by similar water content volume, may differ in area. Moreover, an increase in maximum depth of basins does not necessarily imply any grow in their volume. Likewise, there is no prevalent dependence between basin area and maximum depth. The cluster analysis, among reasonable indications, singled out generally divisions of the considered lakes into two sets. One of the sets comprises Duży Staw and Dziki Staw, while the other consists of all the remaining lakes. Less frequent divisions into three indicated Duży Staw, Dziki Staw, and Czwarty Staw as leading lakes. Divisions into 19–22 clusters were also suggested, however it does not seem to be reliable. As a consequence, the cluster analysis elucidate that Duży Staw and Dziki Staw stand out the most from the other lakes. This remainder constitutes rather close to each other, but not an ideally uniform group of lakes.